Effect of an 11-week in-water training program with increased resistance on the swimming performance and the basic kinematic characteristics of the front crawl stroke - Gourgoulis, V.; Valkoumas, I.; Boli, A.; Aggeloussis, N.; Antoniou, P. (The Journal of Strength and Conditioning Research, 2019)
The purpose of the study was to assess the effect of an 11-week in-water training program with increased resistance on the swimming performance and the basic kinematic characteristics of the front crawl stroke in young female swimmers. Twelve swimmers were matched in pairs according to their best performance in 50-m front crawl swimming and then were randomly assigned to an experimental or to a control group. Both groups followed exactly the same swimming training program. The only exception was that the experimental group performed a sprint training section with increased resistance pulling a water parachute, whereas the control group performed the same section without parachute. Before and after the intervention program, the best performance of both groups in 50-, 100-, and 200-m front crawl swimming were assessed. Moreover, the basic kinematic characteristics of the stroke were calculated during 50-m front crawl swimming with maximal intensity. Two-way repeated measures analyses of variance revealed significant improvement in the best performance in all swimming distances only in the experimental group (3.22-7.26%). As far as the basic kinematic characteristics of the stroke are concerned, significant modifications were found only in the mean swimming velocity in the experimental group (2.18%), whereas no significant changes were observed in the stroke length, the stroke rate, and the duration of the propulsive, and nonpropulsive phases in both groups. Thus, the findings of the current study revealed a positive effect of the in-water resistance training program in the swimming performance of young female swimmers of moderate performance level, without any negative influence in the basic kinematic characteristics of the stroke.